Comparative Analysis of miRNA Expression Profiles of Yak Milk-Derived Exosomes at Different Altitudes - Wenwen Ren; Yongfu La; Xiaoming Ma; Xiaoyun Wu; Xian Guo; Min Chu; Ping Yan; Xianyong Lan; Chunnian Liang (Animals)
Yaks are a rare and unique animal species inhabiting the Qinghai–Tibet Plateau; they are renowned for their remarkable ability to thrive in harsh environments. Milk-derived exosomes, tiny vesicles containing various biological molecules, play crucial roles in numerous pathological and physiological processes, including cell growth, development, and immune regulation. This study delved into the microRNA expression profiles of yak milk-derived exosomes collected from both high- and low-altitude populations using small RNA sequencing. These miRNAs were found to be implicated in pathways associated with mammary gland inflammation, virus infection regulation, and heat stress response. Functional enrichment analyses, utilizing GO and KEGG databases, revealed that the target genes of these differentially expressed miRNAs are enriched in signaling pathways crucial for Th17 cell differentiation and the Ras-MAPK signaling pathway. In conclusion, this research illuminates the adaptive mechanisms of yaks through the differential expression of miRNAs in their milk-derived exosomes across varying environmental conditions. These findings provide a valuable foundation for future investigations into yak resilience and the potential of milk-derived exosomes as tools for disease management and immune modulation.